Implementation of the Third Space Concept in Higher Education Libraries - Nadina Grebović-Lendo (Društvene i Humanističke Studije, 2025)
The aim of this paper is to present the concept of the library as a third space and to propose a model for higher education libraries within the Bosnian and Herzegovinian university community. The third space refers to a place that is neither home nor work but fosters social interaction and learning. With the advancement of library and information services, higher education libraries have evolved into dynamic and sustainable spaces that shape an individual’s educational experience and provide essential resources for education, research, and public engagement. The third space concept in libraries encourages user interaction, transforming the library into an open environment that supports a range of activities, including learning and relaxation. The theoretical framework of this concept centers on user needs, highlighting the importance of ongoing research into those needs. Adopting a problem-based approach, this paper analyzes examples of best practices and explores their potential application in Bosnia and Herzegovina. The research findings indicate that the third space model for higher education libraries can create a stimulating learning environment, fostering a sense of belonging through content-functional and spatial-architectural elements.